Optical and structural studies of graphene-polyvinyl alcohol based thin film for potential sensing of carbaryl using surface plasmon resonance spectroscopy - Muhamad Fauzi, Nurul 'Illya (2022)
Pesticides are commonly employed in modern agriculture to improve crop yield, and these could potentially to pollute the environment and endanger human life. Hence, developing a highly sensitive sensing element for pesticide detection is important for food safety and environmental protection. The development of polymer nanomaterials-based optical sensor for monitoring pesticides has attracted great attention in recent years. Aside from the novelty of material, the effectiveness and efficiency of materials as sensing layers also should be highlighted. Therefore, the aim of this research is to incorporate graphene nanomaterials and synthetic polymer materials in enhancing the detection properties towards carbaryl based surface plasmon resonance sensor. Herein two different sensing layers based thin film presented, i.e., graphene oxide-polyvinyl alcohol (GO-PVA) and graphene quantum dots-polyvinyl alcohol (GQDs-PVA). The structural properties of both thin films were characterized by Fourier transform infrared (FTIR) spectroscopy had confirmed the presence of functional groups in the composites such as hydroxyl, carbonyl, carboxyl, epoxy and alkoxy. Then, the atomic force microscopy (AFM) shows that the roughness of thin films increased for GO-PVA and GQDs-PVA thin films compared to single element, which shows that the surface morphology influenced by the presence of graphene and PVA. Meanwhile, the optical properties of synthesized thin films were investigated using Ultraviolet-visible (UV-vis) spectroscopy and surface plasmon resonance (SPR) spectroscopy. Based on the UV-vis analysis, the absorbance peaks for the thin films can be observed at the wavelength around 200–500 nm and the band gap obtained for both thin films are 4.086 eV and 4.114 eV for GO-PVA and GQDs-PVA thin films, respectively. Then, the proposed thin films have been incorporated with SPR sensor to evaluate the effectiveness and efficiency for carbaryl detection. From that experimental result, GO-PVA thin film exhibited an excellent SPR sensor’s performance with sensitivity at 14.174° ppb-1 with correlation coefficient of 0.999, while the sensitivity of the GQDs-PVA thin film was 8.636° ppb-1 with a correlation coefficient of 0.995. The sensitivity for both these thin films was achieved at a carbaryl concentration of 0.001 ppb, indicating the best concentration limit obtained so far. As conclusion, this study successfully demonstrated an effective new sensing layer that potentially can detect carbaryl pesticide and proved that GO-PVA thin film has a better sensing property compared to GQDs-PVA thin film. This is due to the GO-PVA sensing performance, which is able to identify 0.001 carbaryl with full width at half maximum (FWHM) of 2.878° and high detection accuracy (DA) with single noise to ratio (SNR) values of 0.347 degree 1 and 0.194, respectively.